تأثير التوظيف الإلكتروني على الاستقطاب الفعال للكفاءات في البنوك التجارية الناشطة في ولاية سطيف الجزائرية. - معيوف, هدى; زواوي, خالصة (جامعة الوادي - University of Eloued, 2019)
هدفت الدراسة إلى معرفة تأثير التوظيف الإلكتروني على الاستقطاب الفعال للكفاءات للبنوك الجزائرية، من خلال معرفة دوره في استقطاب الكفاءة ذات الابعاد الثلاثة (المعرفة، المعرفة الفنية، المعرفة الذاتية)، ولقد تم الاعتماد على الاستمارة لغرض جمع البيانات من البنوك محل الدراسة والتي بلغ عددها (18) بنك، وتم استخدام الرزمة الاحصائية للعلوم الاجتماعية (SPSS) لتحليل بيانات الاستمارة، وقد توصلت الدراسة إلى مجموعة من النتائج كان أبرزها أن هناك دور إيجابي التوظيف الالكتروني في الاستقطاب لفعال للكفاءات. This resaerch was aimed to have a vision about the effect of e-employment on the effectiveness of the competencies polirazation in the algerian banks ,through the awareness of its role to attract the competencies with their three dimensions (knowledge, technical knowledge,and self-knowledge). The questionnaire was adapted to gather data from banks where the stady took place which their numbers were18. The Statistical Package for Social Sciences (SPSS) was used to analyze the results were found in the questionnaire. The research found numerous result ,most important is that there a positive role e-employment to attract the effective competencies polirization.
مقال
Keywords: تاهيل ; كفاءات ; بنك